Case Study and Learning Outcomes: prototype for measurement of biomechanical signals of walking based on embedded systems (LACCEI, 2024)
In this article, we discuss learning outcomes in the context of engineering and technology development. The academic space in which the case study is developed is designed to be developed in a research and innovation environment, with the support of the university's research groups. Although the academic space is within the framework established by the university, with a defined number of working hours per week, given its nature, the learning outcomes must be updated for the development of each particular project. In this sense, we show a case study in which a prototype is developed to measure kinematic signals and electromyography that can be used in lower limb exoskeletons. The device is built as a network of low-energy consumption sensors. This document contains the definition of the particular model for the implementation of learning outcomes, the definition of learning outcomes, a description of the methodology for the implementation of said model, and a description of the evaluation and follow-up mechanisms. Also, the methodological development of the project is explained from an engineering point of view, including the sensor network, the sensory fusion strategy, the signal processing, and the results when using the device in an experiment with a healthy user.